Extramarital Sex Among Vietnamese Married Men: Results of a Survey in Urban and Rural Areas of Northern and Southern Vietnam. Issue 9 (21st November 2016) - Nguyen, Huong; Shiu, Cheng-Shi; Hardesty, Melissa
Abstract : Research on extramarital sex (EMS) is commonly conducted from a perspective that implicitly understands this behavior as a violation of the marital relationship. In contrast, Vietnamese cultural norms have, at some points in history, condoned if not outright encouraged EMS in the name of preserving family lineage. Yet little is known about the prevalence of EMS among contemporary Vietnamese men and its association with marriage quality. This is a notable gap, given the enormous sociocultural and ideological shifts the country has experienced over the past several decades. Drawing upon a sample of 126 married men (Mean age = 45.56; SD  = 10.52) surveyed in urban (Hanoi and Ho Chi Minh City) and rural areas (Ha Tay and Can Tho) in Vietnam, we examined the relationship between EMS and geographic region, demographic characteristics, sexual values, quality of marriage, and sexual satisfaction within marriage. Our results show that geographic location had a strong impact on EMS, while most marital relationship quality variables did not impact the odds of EMS for married men in Vietnam.